2023
DOI: 10.3389/fmicb.2023.1112245
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, and pathogenicity analysis of newly emerging gosling astrovirus in South China

Abstract: Goose astroviruses (GoAstV) cause fatal gout and decrease product performance in the waterfowl industry across the world. Since no effective vaccines are available, studies on the epidemiology of the virus are necessary for vaccine development. In this study, we collected 94 gout samples from goose farms in the Guangdong Province of South China. Among them, 87 samples (92.6%) tested positive for GoAstV, out of which five GoAstV strains were isolated after four generations of blind transmission through healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Previous studies have shown that the mortality rate of goose embryos inoculated with GAstV is as high as 100%. This infection not only severely hinders embryonic development, leading to a significant decline in hatchability, but also causes severe hemorrhage in goose embryos [24]. In this study, we successfully isolated eight GAstV strains from clinical samples and infected goose embryos and observed symptoms similar to those reported in previous research.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have shown that the mortality rate of goose embryos inoculated with GAstV is as high as 100%. This infection not only severely hinders embryonic development, leading to a significant decline in hatchability, but also causes severe hemorrhage in goose embryos [24]. In this study, we successfully isolated eight GAstV strains from clinical samples and infected goose embryos and observed symptoms similar to those reported in previous research.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have confirmed that the uric acid content in the serum of goslings infected with GAstV significantly increases, reaching a level of 3800 µmol/L on the 15th day post-infection [24]. Previous research revealed that the enzymatic activities and expression levels of xanthine oxidase (XOD) and adenosine deaminase (ADA) in the livers of goslings infected with GAstV are significantly elevated, showing a clear difference compared to those in the livers of uninfected control goslings.…”
Section: Discussionmentioning
confidence: 82%